Does attempting talc pleurodesis affect subsequent indwelling pleural catheter (IPC)-related non-draining septated pleural effusion and IPC-related spontaneous pleurodesis?. Issue 1 (1st February 2019) - Asciak, Rachelle; Mercer, Rachel M.; Hallifax, Robert J.; Hassan, Maged; Bedawi, Eihab; McCracken, David; Kanellakis, Nikolaos I.; Wrightson, John M.; Psallidas, Ioannis; Rahman, Najib M.
Malignant pleural effusions (MPE) are common and associated with disabling symptoms, and large hospitalisation costs [1]. Current management of recurrent MPE is symptomatic, with chest drain and talc pleurodesis, or indwelling pleural catheter (IPC) insertion. IPCs are an increasingly attractive option in patients wishing to avoid hospitalisation as they reduce initial length of stay [2, 3], but require repeated domiciliary drainage. Other patients opt for talc pleurodesis because, if successful, it represents a one-time definitive procedure, but it has a modest failure rate (20–30%) [4]. In the case of talc pleurodesis failure, IPC insertion is usually advocated with the consequence that a subset of patients with IPC in situ will have previously received ipsilateral intrapleural talc. IPCs are also increasingly being used in patients with recurrent benign pleural effusions (non-MPE) [5, 6]. Prior talc pleurodesis does not result in worsened outcomes from subsequent indwelling pleural catheter use, and patients should not be dissuaded from choosing talc as a primary treatment for recurrent pleural effusion. http://ow.ly/qAAC30mYmr3